Safety and efficacy of a feed additive consisting of narasin (Monteban® G100) for chickens for fattening (Elanco GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of the coccidiostat narasin (Monteban® G100) for chickens for fattening. In a previous opinion, uncertainties remained on the identification and characterisation of the non‐genetically modified production strain of the active substance narasin. The Panel could not conclude either on the safety of Monteban® G100 for chickens for fattening or on the efficacy of the additive at the minimum applied concentration. The FEEDAP Panel excluded risks for environment but the risk for sediment compartment could not be assessed. The applicant provided supplementary information to cover the data gaps and substituted the narasin production strain from Streptomyces spp. NRRL 8092 to Streptomyces spp. NRRL B‐67771. The information submitted to taxonomically identify the production strain did not allow to assign it to any described microbial species. Based on the information provided, the Panel concluded that the use of Monteban® G100 did not raise safety concerns as regards the production strain for the target animal, consumer, user and environment. The Panel concluded that 70 mg narasin/kg complete feed was safe for chickens for fattening with a margin of safety of 1.4; narasin from Monteban® G100 was unlikely to increase shedding of Salmonella Enteritidis, Salmonella Typhimurium and Campylobacter jejuni. Narasin, when used in chickens for fattening at 70 mg/kg feed, was not expected to pose a risk to the aquatic compartment and to sediment, while a risk for the terrestrial compartment could not be excluded. No risk for groundwater was expected, nor for secondary poisoning via the terrestrial food chain, but the risk of secondary poisoning via the aquatic food chain could not be excluded. The Panel concluded that 60 mg narasin/kg feed was efficacious in controlling coccidiosis in chickens for fattening.